Kesesuaian Besar Porsi Nasi Yang Disajikan Dengan Standar Porsi Pada Menu Makanan Biasa - Sundusil Arsyih; Reni Sofiyatin; Suhaema Suhaema (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background. Large portions are often wrong when serving food for patients in hospitals, especially in food serving. There is still an excess and lack of food portions in the hospital because there is no right size in the consumption of rice. This food consumption must be in accordance with the standard portions that have been set. The portion of rice will have a direct effect on the nutritional value contained in food, especially on the nutritional value of carbohydrates which contribute a considerable amount of energy. The purpose of this study was to find out the standard portions, large portions and standard suitability of portions of rice with large portions of rice served at Sanjiwani Hospital Gianyar Regency. Research Methods. The method used in this research is descriptive observational method with crossectional approach. Research Result. The study was conducted on April 22-24 2019 in Sanjiwani General Hospital, Gianyar Regency with a total sample of 30 servings of rice served on a regular food menu which was observed in 3 servants. The proportion of portions served is measured by the food weighing method for 3 days. The results of this study indicate that the average portion of rice produced by SL servitude is 182.2 grams, IKW is 200.6 grams and KW is 176.3 grams. So that it can be concluded that the suitability of the portion of rice served by 3 average servings is not suitable because it is less than the standard portion.